Jihadist Extremism in Spanish Prisons: Characterisation of the Inmates Linked to Jihadist Radicalisation and Analysis of Their Behaviour in Prison - Santos-Hermoso, Jorge (Terrorism and political violence, 2023)
In Spain, 10.1 percent of jihadist terrorists were radicalised in prison. The objective of this paper is to elaborate on the analysis of the phenomenon of jihadist radicalisation in Spain’s prisons by analysing the inmates linked to jihadist radicalisation who are included in groups A, B and C. The results show that the profile of the inmates linked to jihadist radicalisation has not undergone major changes, although a drop in age and an increase in the number of cases of Spanish nationality can be observed. When the inmates included in the three groups were compared at the time of the investigation (August 2019), it was found that they are of a similar age, that Spanish citizens are more common in group A, mental disorders are more common in group C and that both group B as well as C exhibit a more extensive criminal record and more admissions to prison. Important differences were found with regard to the behaviour in prison, namely that the inmates in group A are not individuals who repeatedly employ violence, while the inmates in group C exhibit a very pronounced antisocial profile, with frequent use of both verbal and physical violence in their day-to-day life in prison.